Pengaruh work-life balance terhadap kinerja pegawai dengan komitmen organisasi sebagai variabel intervening - Putri, Naurisydah Hana Yunia; Hadi, Hafid Kholidi (Jurnal Ilmu Manajemen, 2024)
This research aims to measure and analyze the influence of work-life balance on employee performance with organizational commitment as an intervening variable at Puskesmas X. This research is causal research that uses a quantitative approach. The sampling technique used is total sampling with a total of 56 employees. Data were analyzed using partial least square (PLS) technique with SmartPLS 4.1 software. The results of this research prove that work-life balance has a positive and significant effect on employee performance, work-life balance has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on employee performance, organizational commitment did not successfully mediate the effect of work-life balance on employee performance. This research means that if an institution wants to increase employee performances, the institution must be able to provide good work-life balance. In additions, it is recommended to examine other variabels outside the research variables.